Spectre du Laplacien agissant sur les $r$-tenseurs symétriques sur l’espace hyperbolique - Delay, Erwann (Comptes Rendus. Mathématique, 2021)
On the hyperbolic space, we give the spectrum of the Laplacian acting on trace free symmetric tensors fields of any rank.